Torsade de pointes A rare cause of syncope in severe aortic stenosis - MUTLU, BÜLENT; SÜNBÜL, MURAT; ERDOĞAN, OKAN (URBAN & VOGEL, 2013)
The evaluation of syncope in severe aortic stenosis usually requires intense work-up. Mechanical obstruction should not always be implicated as the underlying cause of syncope. Syncope at rest may be rarely associated with ventricular arrhythmias. We present a patient with severe aortic stenosis who experienced syncopal events due to torsade de pointes.
Keywords: Aortic stenosis; Syncope; Sudden death; Therapy; Arrhythmia; PATIENT